2006
DOI: 10.1089/jpm.2006.9.1271
|View full text |Cite
|
Sign up to set email alerts
|

General Practitioners' Attitudes to Palliative Care: A Western Australian Rural Perspective

Abstract: Education and training for rural GPs needs to be relevant to the local context and needs to focus on emotions and beliefs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(98 citation statements)
references
References 36 publications
5
92
0
1
Order By: Relevance
“…finding from a qualitative study by the first author of this paper was that GPs found dealing with family members of palliative care patients to be extremely stressful. 34 One difficulty that emerged strongly was the need to 'juggle' the time constraints of running a busy business with the need to be compassionate, and this was particularly challenging after the patient had died and the bereaved family member wanted to talk. This juggling and the need to change focus are certainly not particular to community pharmacists; research with health care professionals, looking at eliciting and responding to emotional cues, highlights strategies for prioritizing and supporting patients and carers in busy health care settings.…”
Section: Discussionmentioning
confidence: 99%
“…finding from a qualitative study by the first author of this paper was that GPs found dealing with family members of palliative care patients to be extremely stressful. 34 One difficulty that emerged strongly was the need to 'juggle' the time constraints of running a busy business with the need to be compassionate, and this was particularly challenging after the patient had died and the bereaved family member wanted to talk. This juggling and the need to change focus are certainly not particular to community pharmacists; research with health care professionals, looking at eliciting and responding to emotional cues, highlights strategies for prioritizing and supporting patients and carers in busy health care settings.…”
Section: Discussionmentioning
confidence: 99%
“…(24) In many countries, the multidisciplinary care team also has a responsibility to plan together for access to palliative care. (25,26) Factors related to the practice styles of medical and allied health professionals may facilitate referral, or lead to referral delays. (27,28) Despite their gate-keeping role, 78% of doctors in one US study felt that palliative care services were underutilised.…”
Section: Patient and Family-related Issuesmentioning
confidence: 99%
“…Difficulties in communicating prognoses with patients and families have been reported in other studies. (9,26) The ability to communicate honestly and openly in regards to prognosis, end-of-life issues, and information about PC is an important aspect of access to PC services. (24) A survey of US doctors revealed they tended to be optimistic regarding prognosis, especially where the doctors perceived their patients as optimistic regarding the outcome of treatment.…”
Section: Patient and Family-related Issuesmentioning
confidence: 99%
“…Similarly, in a recent survey of nursing homes in the United States, 63% of homes reported being dissatisfied with the training of staff on death and dying (Moss, Braunschwieg, & Rubinstein, 2002). In a recent Australian study of general practitioners' attitudes to palliative care, the general practitioners articulated a strong desire for professional development related to bereavement support (O'Connor & Lee-Steere, 2006). These studies and reviews highlight that the grief education of health providers is overlooked on the whole, and when it does exist, it is narrow in focus.…”
Section: Grief Educationmentioning
confidence: 99%